A Modular Flow Design for the meta‐Selective C−H Arylation of Anilines. Issue 25 (22nd May 2017) - Gemoets, Hannes P. L.; Laudadio, Gabriele; Verstraete, Kirsten; Hessel, Volker; Noël, Timothy
Abstract: Described herein is an effective and practical modular flow design for the meta ‐selective C−H arylation of anilines. The design consists of four continuous‐flow modules (i.e., diaryliodonium salt synthesis, meta ‐selective C−H arylation, inline copper extraction, and aniline deprotection) which can be operated either individually or consecutively to provide direct access to meta ‐arylated anilines. With a total residence time of 1 hour, the desired product could be obtained in high yield and excellent purity without the need for column chromatography, and the residual copper content meets the standards for parenterally administered pharmaceutical substances. Abstract : One by one or all in one : meta ‐Arylated anilines are key moieties in a variety of high‐value chemicals. To access these compounds, four key flow steps were identified, including synthesis of the diaryliodonium salt, meta ‐selective C−H arylation, and the removal of both the copper catalyst and the directing group. Each module has great individual potential, however, combining them allowed straightforward access to meta ‐arylated anilines within a reasonable time scale and with good purity.